2019
DOI: 10.1155/2019/1713801
|View full text |Cite
|
Sign up to set email alerts
|

A Density Peak Clustering Algorithm Based on the K‐Nearest Shannon Entropy and Tissue‐Like P System

Abstract: This study proposes a novel method to calculate the density of the data points based on K-nearest neighbors and Shannon entropy. A variant of tissue-like P systems with active membranes is introduced to realize the clustering process. The new variant of tissue-like P systems can improve the efficiency of the algorithm and reduce the computation complexity. Finally, experimental results on synthetic and real-world datasets show that the new method is more effective than the other state-of-the-art clustering met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In this study, we use a radius d c to define the neighborhood, and subsequently, calculate the density of a data point [10,15]. Some other studies calculate the density of a data point using the distance to the data point's k nearest neighbor [18][19][20][21]. However, the proper value for either d c or k depends on the characteristic of the dataset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we use a radius d c to define the neighborhood, and subsequently, calculate the density of a data point [10,15]. Some other studies calculate the density of a data point using the distance to the data point's k nearest neighbor [18][19][20][21]. However, the proper value for either d c or k depends on the characteristic of the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…For example, [16] applied the concept of heat diffusion and [17] employed the potential entropy of the data field to assist in setting the radius . Also, many studies suggested using k nearest neighbors to define density, instead of using the radius [18][19][20][21]. Furthermore, [22] suggested calculating two kinds of densities, one based on k nearest neighbors and one based on local spatial position deviation, to handle datasets with mixed density clusters.…”
Section: Variants Of Dpcmentioning
confidence: 99%
See 2 more Smart Citations
“…Various meta-heuristic algorithms, such as GA [69], DE [70] and its variants [71,72], PSO [73,74], ABC [75], and BBO [76], are usually introduced to SNS-based MIEAs as the basic evolutionary operation in the cell or neural [77][78][79][80][81]. The membrane structure in DNS-based MIEAs can be dynamically changed according to communication channel rules, and this class of MIEAs, with an extended membrane structure, has great potential for solving complex problems [82,83]. For another kind of EMC, ADMCMs are designed to overcome the complex programmability of membranebased modes, and the automated synthesis of computing models by applying various meta-heuristic methods can be obtained through this class of EMC [84][85][86].…”
Section: Introductionmentioning
confidence: 99%